A reporting guideline for clinical platelet transfusion studies from the BEST Collaborative. Issue 6 (25th September 2012) - Meyer, Erin; Delaney, Meghan; Lin, Yulia; Morris, Anna; Pavenski, Katerina; Tinmouth, Alan; Murphy, Mike; Slichter, Sherrill J.; Heddle, Nancy; Dumont, Larry J.
<x xml:space="preserve">Abstract</x> BACKGROUND: A systematic review of randomized controlled trials and observational studies assessing platelet (PLT) transfusion therapy identified gaps in the descriptions of trial design, variables of the PLT products transfused, and outcomes. We aimed to systematically develop a reporting guideline to aid in designing, reporting, and critiquing PLT trials. STUDY DESIGN AND METHODS: With the use of expert opinion, a preliminary checklist of 23 items was created. The Delphi method, an iterative forecasting method, was used to achieve consensus among experts to systematically improve upon the preliminary checklist. Items were ranked for inclusion using a 7‐point Likert scale from "definitely should not" to "very important to" include. Criteria were established a priori based on the mean score: at least 5.5 accept, 2.6 to 5.4 intermediate, and not more than 2.5 eliminate. Intermediate items were edited and sent out in subsequent rounds for review. Three rounds were undertaken to determine the final checklist. RESULTS: Initially 33 experts participated, decreasing to 25 by the third round. The preliminary checklist consisted of 23 items spread over four sections: methods and intervention, PLT‐specific outcomes, PLT‐specific results, and PLT‐specific adverse events. After three rounds of the Delphi method, the checklist was expanded and refined to include 30 items. The final checklist was further enhanced by adding an explanatory guide. CONCLUSION: Use of the Delphi method was successful in finding consensus on items to include in reports of a clinical PLT transfusion study. The final checklist and explanatory guide will be useful for authors and editors to improve the reporting of PLT transfusion trials.